2016
DOI: 10.1038/srep22010
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion of Fukushima-derived radiocaesium into subsurface water due to formation of mode waters in the North Pacific

Abstract: The Fukushima Dai-ichi Nuclear Power Plant accident in March 2011 released radiocaesium (137Cs and 134Cs) into the North Pacific Ocean. Meridional transects of the vertical distribution of radiocaesium in seawater were measured along 147 °E and 155 °E in October–November 2012, 19 months after the accident. These measurements revealed subsurface peaks in radiocaesium concentrations at locations corresponding to two mode waters, Subtropical Mode Water and Central Mode Water. Mode water is a layer of almost verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 51 publications
(124 reference statements)
3
44
0
Order By: Relevance
“…Kaeriyama et al . () also reported the Fukushima‐derived radioactive Cs in the CMW at just north of KE along 155˚E during October–November 2012. Yoshida et al .…”
Section: Subsurface Intrusion Of Radioactive Cesium With Mode Watersmentioning
confidence: 87%
See 3 more Smart Citations
“…Kaeriyama et al . () also reported the Fukushima‐derived radioactive Cs in the CMW at just north of KE along 155˚E during October–November 2012. Yoshida et al .…”
Section: Subsurface Intrusion Of Radioactive Cesium With Mode Watersmentioning
confidence: 87%
“…After the FNPP accident, subsurface intrusion of Fukushima-derived radioactive Cs associated with these mode waters has been reported (Kitamura et al, 2013;Kumamoto et al, 2013Kumamoto et al, , 2014Kaeriyama et al, 2014Kaeriyama et al, , 2016Aoyama et al, 2015b;Men et al, 2015;Yoshida et al, 2015). Kitamura et al (2013), Kumamoto et al (2013Kumamoto et al ( , 2014 reported the subsurface peak of Fukushima-derived radioactive Cs within STMW along 149˚E during December 2011-February 2012, in the subtropical region far south from the FNPP-site and just south of KE.…”
Section: Subsurface Intrusion Of Radioactive Cesium With Mode Watersmentioning
confidence: 99%
See 2 more Smart Citations
“…These were drawn using Ocean Data View software 55) and redrawn from , 147°E observed in November 2012 (b) 50) , 155°E observed in October 2012 (c) 50) , and 165°E observed between June and July 2012 (d) 30) . Contour intervals of Fig.…”
mentioning
confidence: 99%